Avaliação audiológica em pacientes com mucopolissacaridose: estudo da ocorrência, tipo e grau de perda auditiva - Silveira, Marcela Rosana Maia da [UNIFESP] (2011)
Purpose: the mucopolysaccharidosis are a group of diseases caused by a deficiency in the lysosomal enzymes involved in the metabolism of mucopolysaccharides. Inherited metabolic diseases are caused by inborn errors of metabolism that lead to lack of proper functioning of certain enzymes. Hearing loss is a frequent manifestation in patients with mucopolysaccharidosis. The progressive nature of the hearing loss program requires audiologic, with periodic evaluations of the hearing. General objective: check the occurrence of hearing loss, characterizing its type and grade in patients with mucopolysaccharidosis. Specific objectives: aimed at verifying the possibility to evaluate patients with MPS and establish more effective procedures for hearing assessment in relation to age and type of MPS. Method: We evaluated 60 (sixty) patients, between 2 and 23 years, 25 females and 35 males with a diagnosis of different types of MPS, conducted by geneticist. Selected patients underwent audiometric assessment . The procedure for obtaining auditory thresholds were chosen according to the chronological age of the patient and also considering their position to understand / respond to the procedure. Results: Of the 60 patients studied, 53 (88.3%) completed the diagnostic audiology. Of these, 51 (96.2%) had hearing loss being the most conductive 25 (47.2%). There was no difference between the hearing thresholds by air and bone conduction thresholds logoaudiometric between the ears. There was a higher incidence of female patients in types I, III and IV of MPS and males in the types II and VI. Regarding the procedures used, pure tone audiometry was performed in patients over the types of MPS IV and VI. Type II patients performed more visual reinforcement audiometry. Sensorineural hearing loss occurred in patients with MPS type I, II and III. Type III patients had worse hearing thresholds obtained by bone and increased occurrence of type A tympanometric curves with the presence of acoustic reflex. Type IV patients showed a predominance of normal audiograms, with hearing thresholds better than others and increased occurrence of type A tympanometric curves. The type I showed more mixed hearing loss. There was a higher incidence of conductive hearing loss in type II, IV and VI of MPS with a higher incidence of tympanometric curves of type B and C in the absence of acoustic reflex. Conclusions: the audiological evaluation can be performed in 88,3% of the population; there was hearing loss in 96.2% of patients with MPS, with a predominantly conductive hearing loss of mild and moderately severe; was occurrence of sensorineural hearing loss in patients with MPS type I, II and III.